The God concept among Muslim children (aged 6) : a case of Tadika Khalifah Bestari - Maryam binti Jailani (2011)
Since 'aqīdah is the bedrock of Islam, the belief in Allah should be inculcated since young. However, the data on the concept of God among Muslim children are not currently available. Therefore, the objective of this research is to analyze the concept of God among Muslim children; particularly at Tadika Khalifah Bestari. The data is collected through semi-structured interviews with six respondents. The interview questions are set by specifying the operational definitions of the concept of God in Islam, as well as according to the scope set by the Kurikulum Standard Prasekolah Kebangsaan (National Standard Curriculum for Preschool) and the curriculum of Tadika Khalifah Bestari itself. From the findings, it could be seen that the children's basic understanding of the concept of God is good. In addition, many parties have contributed to the respondents' belief, but their mothers are the most dominant compared to others. The findings of this study will benefit many parties involved in the education process of young children. It will also show the result of faith education on Muslim children; particularly at Tadika Khalifah Bestari as compared to the guideline laid down in Islam.